Multi-gradient composite prepreg and preparation method thereof
By combining the multi-gradient composite structure of chopped and continuous glass fiber fabrics in the prepreg, the problem of insufficient fluidity of the existing prepreg is solved, and the mechanical properties and flame retardant properties of the composite are significantly improved, and suitable for complex structures. and high strength requirements.
Patent Information
- Application Number
- CN202411620216.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-14
AI Technical Summary
When pressing parts with complex structures, existing prepregs are prone to structural defects such as material shortages, sand holes, etc. When pressing parts with complex structures, they are prone to structural defects and appearance defects such as material defects, and the strength of short-cut fiber prepregs is low, making it difficult to meet the strength requirements of high bearing capacity. Component requirements.
Using multi-gradient composite prepregs, combining 50-65% epoxy resin composition and 35-50% fiber reinforced materials, including chopped glass fibers and continuous glass fiber fabrics, to form "short-long-short" or " Short-long" composite structures are prepared by specific impregnation and yarn cutting processes to improve fluidity and strength.
The fluidity and molding quality of complex parts are improved, and the tensile, bending and impact strength of the material is improved. The tensile modulus reaches more than 16GPa, the bending modulus and impact strength are significantly improved, and the flame retardant performance is also achieved. UL94 2.0mmV0 standard.
Smart Images

Figure CN119307067A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of prepregs, and in particular to a multi-gradient composite prepreg and a preparation method thereof. Background Art
[0002] Prepreg is a resin matrix / reinforcement material combination made by impregnating continuous fibers, fabrics and chopped fibers with a resin matrix under certain conditions. It is a material form for manufacturing advanced composite components. The reinforcing material of prepreg is usually a single continuous fiber, fabric, or a single chopped fiber. The advantage of continuous fiber prepreg is its high strength, but when pressing parts with complex structures, it is prone to structural and appearance defects such as material shortages and sand holes due to insufficient fluidity. The advantage of chopped fiber prepreg is that when pressing products with complex structures, it has good fluidity and can ensure the quality of fine structure molding on the product surface, but the strength of chopped fiber prepreg is lower than that of continuous fiber prepreg, and it is not suitable for load-bearing parts with high strength requirements. Summary of the invention
[0003] In order to solve the above technical problems, the present invention is proposed. The present invention provides a multi-gradient composite prepreg and a preparation method thereof, which solves the technical problem in the prior art that when pressing a structured component, structural and appearance defects such as material shortage and sand holes are easily caused due to insufficient fluidity.
[0004] According to one aspect of the present invention, the present invention provides a multi-gradient composite prepreg, comprising 50-65% by weight of an epoxy resin composition and 35-50% by weight of a fiber reinforcement material, wherein the fiber reinforcement material comprises chopped glass fibers and continuous glass fiber fabric, and the continuous glass fiber fabric is a continuous glass fiber woven cloth;
[0005] The continuous glass fiber woven cloth roll is placed between the front tangent roller and the rear tangent roller where the yarn is dropped, to form a "short-long-short" composite prepreg structure of "chopped glass fiber-continuous glass fiber-chopped glass fiber"; or the continuous glass fiber woven cloth roll is placed behind the rear tangent roller where the yarn is dropped, to form a "short-long" composite prepreg structure of "chopped glass fiber-continuous glass fiber".
[0006] Preferably, the epoxy resin composition is prepared from the following raw materials in parts by weight:
[0007]
[0008] Preferably, the epoxy resin is at least one or more of bisphenol A epoxy resin and bisphenol F epoxy resin; the active diluent is a low molecular compound containing one or more epoxy groups; the latent curing agent is one or more of dicyandiamide, organic acid hydrazide, boron trifluoride-amine complex; the curing accelerator is one or more of tertiary amine, substituted urea, imidazole, modified imidazole; the halogen-free flame retardant is one or more of aluminum hydroxide, halogen-free nitrogen-phosphorus flame retardant, and ammonium polyphosphate; the auxiliary agent is one or more of internal release agent, wetting dispersant, coupling agent, and defoaming agent; the thickener is one or more of 1,3-cyclohexanedimethylamine, 4,4'-diaminodicyclohexylmethane, isophoronediamine, and 1,6-hexanediamine;
[0009] Preferably, the active diluent is at least one or more of benzyl glycidyl ether, 1,4-butanediol diglycidyl ether, trimethylolpropane triglycidyl ether, and tert-butyl glycidyl carbonate; and / or, the bisphenol A type epoxy resin is one of E44 epoxy resin and E51 epoxy resin; and / or, the bisphenol F type epoxy resin is one of Nan Ya NPEF-170, Asahi Denka EP-4901, and Asahi Denka EP-4901E; and / or, the internal mold release agent is BYK-P9912, LubeKote 8172, and LubeKote 6802, one of them; and / or, the wetting and dispersing agent is one of BYK-W903, BYK-W907, BYK-W940, BYK-W9076; and / or, the coupling agent is a silane coupling agent, preferably, the silane coupling agent is one of γ-aminopropyltriethoxysilane (KH550) and γ-glycidyloxypropyltrimethoxysilane (KH560); and / or, the dispersant is one of BYK-W904, BYK-W905, BYK-W906, BYK-W9077; and / or, the coupling agent is a silane coupling agent, preferably, the silane coupling agent is one of γ-aminopropyltriethoxysilane (KH550) and γ-glycidyloxypropyltrimethoxysilane (KH560); and / or, the dispersant is one of BYK-W903, BYK-W907, BYK-W940, BYK-W9076; and / or, the dispersant is one of BYK-W905, BYK-W906 The foaming agent is an organosilicon defoamer, preferably, the organosilicon defoamer is one of BYK-A530 and Deqian 6800; and / or, the organic acid hydrazide is one of adipic acid dihydrazide and sebacic acid dihydrazide; and / or, the tertiary amine is one of DMP-30, tri(2-ethylhexanoate) salt of DMP-30, trioleate of DMP-30, and bicyclic amidine diethylhexanoate; and / or, the substituted urea is Azken DYHARD UR 500, Azken DYHARD UR 300, Huntsman OMICURE U-24M, Huntsman OMICURE U-405M; and / or, the imidazole is one of imidazole, 2-methylimidazole, 1-benzyl-2-ethylimidazole, 2-ethyl-4-methylimidazole; and / or, the modified imidazole is one of Ajinomoto PN-23, Ajinomoto PN-40, Ajinomoto PN-50, Ajinomoto PN-H.
[0010] Preferably, the fiber reinforcement material comprises chopped glass fibers and continuous glass fiber fabric; the chopped glass fibers are obtained by chopping glass fiber plied yarns; and the continuous glass fiber fabric is glass fiber woven cloth.
[0011] Preferably, the length of the chopped glass fibers is 20-50 mm, and the surface density of the continuous glass fiber fabric is 200-400 g / m 2 .
[0012] According to a second aspect of the present invention, the present invention provides a method for preparing a multi-gradient composite prepreg, comprising the following steps: step 1, weighing 80-95 parts of epoxy resin, 5-20 parts of active diluent, and 1-15 parts of auxiliary agent in a mixing tank, stirring evenly, and then sequentially adding 5-15 parts of latent curing agent, 1-5 parts of curing accelerator, and 50-150 parts of halogen-free flame retardant, and performing high-speed stirring and dispersion, and obtaining resin paste A after dispersion; step 2, filtering the resin paste A through an 80-100 mesh filter screen, adding 3-10 parts of thickener in proportion, and performing high-speed stirring and dispersion, and obtaining resin paste B after dispersion; step 3, passing the glass fiber plied yarn through the yarn guide tube through an air gun into the yarn cutting roller, and pouring the resin paste B into the high-position glue tank and the low-position glue tank respectively, turning on the main machine to move the film, and driven by the carrier film, the resin paste B passes through the glue tank on the The gap between the scraper and the tabletop scrapes out a resin film with uniform thickness, the resin film scraped out by the low-position glue groove is the lower resin film, and the resin film scraped out by the high-position glue groove is the upper resin film; step 4, turn on the front cutting roller and the rear cutting roller, and the cutter on the cutting roller uniformly cuts the glass fiber plied yarn into short glass fibers with a length of 20-50 mm, and the short glass fibers fall freely onto the lower resin film in step 3; unfold the glass fiber woven cloth roll and place it between the doffing positions of the front cutting roller and the rear cutting roller, or unfold the continuous glass fiber woven cloth roll and place it behind the doffing position of the rear cutting roller, and the leading edge of the continuous glass fiber woven cloth is laid on the front end of the impregnation zone; the upper resin film is finally covered on the short glass fibers or the glass fiber woven cloth, and enters the impregnation zone through the traction of the guide roller, and the fiber impregnation is completed under the extrusion of the chain belt, and then rolled up and transferred to the drying room for aging, and a multi-gradient composite prepreg is obtained after aging.
[0013] Preferably, the stirring speed in step 1 is 400-600 r / min, the stirring time is 15-30 min, and the viscosity of resin paste A is 12000-35000 mPa·S (40°C); the stirring speed in step 2 is 400-600 r / min, the stirring time is 3-5 min, and the resin temperature is lower than 50°C.
[0014] Preferably, in step 3, the carrying film has a film travel speed of 5-8 m / min; and the gap between the scraper and the table is 0.1-1 mm.
[0015] Preferably, in step 4, the aging temperature is 35-60° C. and the aging time is 3-72 hours.
[0016] Preferably, in step 4, the placement position of the glass fiber woven cloth roll is different, and the structure of the prepared composite prepreg is also different: the glass fiber woven cloth roll is placed between the doffing position of the front tangent roller and the rear tangent roller, the chopped glass fibers obtained by cutting the rear tangent roller will fall onto the glass fiber woven cloth, and then the upper resin film is covered on the chopped glass fibers to form a "short-long-short" structure of "chopped glass fibers-continuous glass fibers-chopped glass fibers"; the glass fiber woven cloth roll is placed behind the doffing position of the rear tangent roller, the glass fiber woven cloth will cover the chopped glass fiber layer obtained by cutting the front tangent roller and the rear tangent roller, and then the upper resin film is covered on the glass fiber woven cloth layer to form a "short-long" structure of "chopped glass fibers-continuous glass fibers".
[0017] The present invention provides a multi-gradient composite prepreg, comprising an epoxy resin composition with a weight percentage of 50-65% and a fiber reinforcement material with a weight percentage of 35-50%; the reinforcement material has both chopped glass fibers and continuous glass fiber fabrics, the chopped glass fiber layer has good fluidity during molding, which is convenient for molding complex parts such as special-shaped parts and reinforced structural parts, and the continuous glass fiber layer gives the material higher strength. The fiber-reinforced composite material prepared using the multi-gradient composite prepreg of the present invention has good mechanical properties, with a tensile strength of more than 220MPa, a tensile modulus of more than 16GPa, a flexural strength of 350MPa, a flexural modulus of more than 16GPa, and an impact strength of 160kJ / m 2 The above, at the same time, the flame retardant performance is good, and the vertical burning performance reaches UL94 2.0mmV0. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The above and other purposes, features and advantages of the present invention will become more apparent by describing the embodiments of the present invention in more detail in conjunction with the accompanying drawings. The accompanying drawings are used to provide a further understanding of the embodiments of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings, the same reference numerals generally represent the same components or steps.
[0019] Figure 1 This is a schematic diagram of the multi-gradient composite prepreg structure of "chopped glass fiber layer + continuous glass fiber woven cloth layer" provided in Example 1 of the present invention;
[0020] Figure 2 This is a schematic diagram of the multi-gradient composite prepreg structure of "chopped glass fiber layer + continuous glass fiber woven cloth layer + chopped glass fiber layer" provided in Examples 2-6 of the present invention;
[0021] Figure 3It is a schematic diagram of the structure of the chopped glass fiber prepreg obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0022] Below, the exemplary embodiments according to the present invention will be described in detail with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments of the present invention, and it should be understood that the present invention is not limited to the exemplary embodiments described here.
[0023] Example 1
[0024] Preparation of resin paste: Weigh 90 parts of E51 epoxy resin, 10 parts of 1,4-butanediol diglycidyl ether (active diluent), 5 parts of internal release agent (BYK-P9912), and 1.2 parts of wetting dispersant (BYK-W903) in a mixing tank, turn on the high-speed disperser for stirring and dispersing, and after stirring evenly, add 15 parts of adipic acid dihydrazide, 1 part of DMP-30 and 120 parts of aluminum hydroxide (aluminum hydroxide is added in 6 times) in turn, and stir and disperse at high speed. The stirring speed is set to 500r / min, the stirring time is 20min, and resin paste A is obtained after stirring; resin paste A is filtered through an 80-mesh filter, 5 parts of 1,3-cyclohexanedimethylamine are added and dispersed at high speed, the stirring speed is set to 500r / min, the stirring time is 4min, and resin paste B is obtained after stirring.
[0025] Prepreg preparation: SMC sheet machine (Laizhou Yaosheng Automation Equipment Co., Ltd.) was used to prepare prepreg.
[0026] ① Preparation: Pass the PP carrier film through the gap between the high-position glue tank and the low-position glue tank and the table surface respectively, set the film feeding speed to 5m / min, and adjust the gap between the scraper of the high-position glue tank and the low-position glue tank and the table surface to 0.55mm; pass the glass fiber plied yarn through the yarn guide tube through the air gun and enter the yarn cutting roller, and pour the resin paste B into the high-position glue tank and the low-position glue tank respectively;
[0027] ② Film scraping: Turn on the main machine to move the film. Driven by the carrier film, the resin paste B passes through the gap between the scraper on the glue tank and the table to scrape out a resin film of uniform thickness. The resin film scraped out of the low-position glue tank is the lower resin film, and the resin film scraped out of the high-position glue tank is the upper resin film;
[0028] ③ Yarn cutting and impregnation: Turn on the front and rear yarn cutting rollers, and the cutters on the yarn cutting rollers uniformly cut the glass fiber plied yarn into short glass fibers with a length of 20-50 mm (in this embodiment, the short glass fibers cut by the front yarn cutting roller are 50 mm long, and the short glass fibers cut by the rear yarn cutting roller are 25 mm long). The short glass fibers fall freely onto the lower resin film, and the continuous glass fiber woven cloth roll (surface density 200 g / m 2) is unfolded and placed behind the doffing position of the rear yarn cutting roller, the continuous glass fiber woven fabric is covered on the short glass fiber layer cut by the front yarn cutting roller and the rear yarn cutting roller, and then the upper resin film is covered on the glass fiber woven fabric layer, the front edge of the glass fiber woven fabric is laid on the front end of the impregnation area, and is pulled into the impregnation area by the guide roller, and the fiber impregnation is completed under the extrusion of the chain belt;
[0029] ④ Rolling and aging: The impregnated prepreg is rolled up and transferred to the drying room for aging at a temperature of 45°C for 15 hours. After aging, a multi-gradient composite prepreg with a structure of "chopped glass fiber layer + continuous glass fiber lattice cloth layer" is obtained.
[0030] Performance test: The composite prepreg was pressed into a 250*250*4mm composite board using a flat vulcanizer, and machined into test specimens. The tensile properties (including tensile strength and tensile modulus) were tested according to GB / T1447-2005, the bending properties (including bending strength and bending modulus) were tested according to GB / T1449-2005, and the impact properties (simple beam unnotched impact strength) were tested according to GB / T1043.1-2008. The tensile and bending properties were tested using a microcomputer-controlled electronic universal testing machine WDW-100M (Jinan Zhongluchang Testing Machine Manufacturing Co., Ltd.), the impact properties were tested using an electronic simple beam impact testing machine XJJD-50 (Chengde Zongchi Testing Instrument Co., Ltd.), and the flame retardant properties were tested according to the vertical method in GB / T2408-2021.
[0031] The test results are shown in Table 1.
[0032] Example 2
[0033] Resin paste preparation: same as Example 1
[0034] Prepreg preparation: Except for the different placement of the continuous glass fiber woven fabric roll, the other steps are the same as in Example 1. In this example, 200 g / m 2 The glass fiber woven fabric roll is placed between the front yarn cutting roller and the rear yarn cutting roller. After the front yarn cutting roller cuts and drops the yarn, the glass fiber woven fabric is covered on the chopped glass fiber. The rear yarn cutting roller cuts and drops the yarn on the glass fiber woven fabric. The upper resin film is finally covered on the chopped glass fiber, and finally a multi-gradient composite prepreg with a "chopped glass fiber layer + continuous glass fiber woven fabric layer + chopped glass fiber layer" structure is obtained.
[0035] Performance test: The composite prepreg was pressed into a 250*250*4 mm composite plate using a flat vulcanizer, and machined into test specimens to test mechanical properties and flame retardancy. The test method and standard were the same as in Example 1. The test results are shown in Table 1.
[0036] Example 3
[0037] Preparation of resin paste: Weigh 80 parts of E51 epoxy resin, 20 parts of trimethylolpropane triglycidyl ether (active diluent), 5 parts of internal release agent (LubeKote 8172), and 1.5 parts of wetting dispersant (BYK-W907) in a mixing tank, turn on the high-speed disperser for stirring and dispersing, and after stirring evenly, add 5 parts of dicyandiamide, 5 parts of imidazole and 150 parts of aluminum hydroxide (aluminum hydroxide is added in 8 times) in turn, and stir and disperse at high speed. The stirring speed is set to 400r / min, the stirring time is 30min, and resin paste A is obtained after stirring; resin paste A is filtered through an 80-mesh filter, 7 parts of isophoronediamine are added and dispersed at high speed, the stirring speed is set to 400r / min, the stirring time is 5min, and resin paste B is obtained after stirring.
[0038] Preparation of prepreg: The operation steps are the same as those in Example 1, except that the film speed is 7 m / min, the gap between the scraper and the table of the high and low glue tanks is 0.75 mm, and the surface density of the glass fiber woven cloth roll is 400 g / m 2 , the curing temperature is 60° C., and the curing time is 3 hours. This embodiment obtains a multi-gradient composite prepreg with a “chopped glass fiber + continuous glass fiber lattice cloth layer” structure.
[0039] Performance test: The composite prepreg was pressed into a 250*250*4 mm composite plate using a flat vulcanizer, and machined into test specimens to test the mechanical properties and flame retardant properties. The test method and standard were the same as in Example 1. The test results are shown in Table 1.
[0040] Example 4
[0041] Resin paste preparation: same as Example 3
[0042] Prepreg preparation: Except for the different placement of the continuous glass fiber woven fabric roll, the other steps are the same as in Example 3. In this example, 400 g / m 2 The glass fiber woven fabric roll is placed between the front yarn cutting roller and the rear yarn cutting roller. After the front yarn cutting roller cuts and drops the yarn, the glass fiber woven fabric is covered on the chopped glass fiber. The rear yarn cutting roller cuts and drops the yarn on the glass fiber woven fabric. The upper resin film is finally covered on the chopped glass fiber, and finally a multi-gradient composite prepreg with a "chopped glass fiber layer + continuous glass fiber woven fabric layer + chopped glass fiber layer" structure is obtained.
[0043] Performance test: The composite prepreg was pressed into a 250*250*4 mm composite plate using a flat vulcanizer, and machined into test specimens to test the mechanical properties and flame retardant properties. The test method was the same as in Example 1. The test results are shown in Table 1.
[0044] Example 5
[0045] Preparation of resin paste: weigh 95 parts of E44 epoxy resin, 5 parts of trimethylolpropane triglycidyl ether (active diluent), 4.5 parts of internal release agent (LubeKote 6802), and 1 part of wetting dispersant (BYK-W940) in a mixing tank, turn on the high-speed disperser for stirring and dispersing, and after stirring evenly, add 7 parts of dicyandiamide, 1 part of UR500 (organic urea accelerator) and 100 parts of aluminum hydroxide (aluminum hydroxide is added in 5 times) in turn, and stir and disperse at high speed. The stirring speed is set to 600r / min, the stirring time is 15min, and resin paste A is obtained after stirring; resin paste A is filtered through an 80-mesh filter, 9 parts of 4,4'-diaminodicyclohexylmethane are added and dispersed at high speed. The stirring speed is set to 600r / min, the stirring time is 3min, and resin paste B is obtained after stirring.
[0046] Preparation of prepreg: The operation steps are the same as those in Example 1, except that the film speed is 8 m / min, the gap between the scraper of the high-position glue tank and the low-position glue tank and the table is 0.65 mm, the aging temperature is 35°C, and the aging time is 24 h. This example obtains a multi-gradient composite prepreg with a "chopped glass fiber layer + continuous glass fiber woven cloth layer" structure.
[0047] Performance test: The composite prepreg was pressed into a 250*250*4 mm composite plate using a flat vulcanizer, and machined into test specimens to test the mechanical properties and flame retardant properties. The test method and standard were the same as in Example 1. The test results are shown in Table 1.
[0048] Example 6
[0049] Resin paste preparation: same as Example 5
[0050] Preparation of prepreg: Except for the different placement of the continuous glass fiber woven fabric roll, the other steps are the same as those in Example 5. In this example, a 200 g / m2 glass fiber woven fabric roll is placed between the front cutting roller and the rear cutting roller, and after the front cutting roller has cut and doffed the yarn, the glass fiber woven fabric is covered on the chopped glass fibers, and the rear cutting roller cuts and doffs the yarn on the glass fiber woven fabric, and the upper resin film is finally covered on the chopped glass fibers, and finally a multi-gradient composite prepreg with a "chopped glass fiber layer + continuous glass fiber woven fabric layer + chopped glass fiber layer" structure is obtained.
[0051] Performance test: The composite prepreg was pressed into a 250*250*4 mm composite plate using a flat vulcanizer, and machined into test specimens to test the mechanical properties and flame retardant properties. The test method was the same as in Example 1. The test results are shown in Table 1.
[0052] Comparative Example 1
[0053] Resin paste preparation: same as Example 5
[0054] Preparation of prepreg: Except for not adding continuous glass fiber woven cloth, other steps are the same as those in Example 5.
[0055] Performance test: The composite prepreg was pressed into a 250*250*4 mm composite plate using a flat vulcanizer, and machined into test specimens to test the mechanical properties and flame retardant properties. The test method and standard were the same as in Example 1. The test results are shown in Table 1.
[0056] Table 1 Test results of resin paste and prepreg properties
[0057]
[0058]
[0059] The tensile, bending, impact and other mechanical properties of the multi-gradient composite prepregs prepared in Examples 1-6 are significantly higher than those of the chopped glass fiber prepregs prepared in the comparative example, indicating that the addition of continuous glass fiber fabrics improves the mechanical strength of the prepregs.
[0060] Examples 1, 3, and 5 are structures of "chopped glass fiber layer + continuous glass fiber woven fabric layer", and Examples 2, 4, and 6 are structures of "chopped glass fiber layer + continuous glass fiber woven fabric layer + chopped glass fiber". Example 1 is compared with Example 2, Example 3 is compared with Example 4, and Example 5 is compared with Example 6. The resin matrix is the same, the fiber structure of the composite prepreg is different, and the mechanical properties are equivalent. This shows that the different structures of the multi-gradient composite prepreg have little effect on the mechanical properties.
[0061] The surface density of the continuous glass fiber woven cloth used in Examples 1, 2, 5, and 6 is 200 g / m2, and the surface density of the glass fiber woven cloth used in Examples 3 and 4 is 400 g / m2. The tensile, bending, impact and other mechanical properties of the multi-gradient composite prepregs prepared in Examples 3 and 4 are slightly higher than those of other examples, indicating that the surface density of the continuous glass fiber has a certain influence on the mechanical properties of the prepreg, and the higher the surface density, the higher the mechanical strength.
[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the concept and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A multi-gradient composite prepreg, characterized in that: The invention comprises 50-65% by weight of an epoxy resin composition and 35-50% by weight of a fiber reinforcement material, wherein the fiber reinforcement material comprises chopped glass fibers and continuous glass fiber fabric, and the continuous glass fiber fabric is a continuous glass fiber woven cloth; The continuous glass fiber woven fabric roll is placed between the front tangent roller and the rear tangent roller doffing position to form a "short-long-short" composite prepreg structure of "chopped glass fiber-continuous glass fiber-chopped glass fiber"; or the continuous glass fiber woven fabric roll is placed behind the doffing position of the rear tangent roller to form a "short-long" composite prepreg structure of "chopped glass fiber-continuous glass fiber".
2. A multi-gradient composite prepreg according to claim 1, characterized in that: The epoxy resin composition is composed of the following raw materials in parts by weight:
3. A multi-gradient composite prepreg according to claim 2, characterized in that: The epoxy resin is one of bisphenol A epoxy resin and bisphenol F epoxy resin; The active diluent is a low molecular weight compound containing one or more epoxy groups; The latent curing agent is at least one or more of dicyandiamide, organic acid hydrazide, and boron trifluoride-amine complex; The curing accelerator is at least one or more of tertiary amine, substituted urea, imidazole, and modified imidazole; The halogen-free flame retardant is at least one or more of aluminum hydroxide, halogen-free nitrogen-phosphorus flame retardant, and ammonium polyphosphate; The auxiliary agent is at least one or more of an internal release agent, a wetting and dispersing agent, a coupling agent, and a defoaming agent; The thickener is at least one or more of 1,3-cyclohexanedimethylamine, 4,4'-diaminodicyclohexylmethane, isophoronediamine, and 1,6-hexanediamine.
4. The multi-gradient composite prepreg according to claim 1, characterized in that: The active diluent is at least one or more of benzyl glycidyl ether, 1,4-butanediol diglycidyl ether, trimethylolpropane triglycidyl ether, and tert-butyl glycidyl carbonate; And / or, the bisphenol A epoxy resin is one of E44 epoxy resin and E51 epoxy resin; And / or, the bisphenol F epoxy resin is one of NPEF-170, EP-4901, and EP-4901E; And / or, the internal release agent is one of BYK-P9912, LubeKote 8172, and LubeKote 6802; And / or, the wetting and dispersing agent is one of BYK-W903, BYK-W907, BYK-W940, BYK-W9076; And / or, the coupling agent is a silane coupling agent, preferably, the silane coupling agent is one of KH550 and KH560; And / or, the defoamer is an organosilicon defoamer, preferably, the organosilicon defoamer is one of BYK-A530 and Deqian 6800; And / or, the organic acid hydrazide is one of adipic acid dihydrazide and sebacic acid dihydrazide; And / or, the tertiary amine is one of DMP-30, tri(2-ethylhexanoate) salt of DMP-30, trioleate of DMP-30, and bicyclic amidine diethylhexanoate; And / or, the substituted urea is one of DYHARD UR 500, DYHARD UR 300, OMICURE U-24M, OMICUREU-405M; And / or, the imidazole is one of imidazole, 2-methylimidazole, 1-benzyl-2-ethylimidazole, and 2-ethyl-4-methylimidazole; And / or, the modified imidazole is one of Ajinomoto PN-23, Ajinomoto PN-40, Ajinomoto PN-50 and Ajinomoto PN-H.
5. The multi-gradient composite prepreg according to claim 4, characterized in that: The fiber reinforcement material comprises chopped glass fibers and continuous glass fiber fabrics. The chopped glass fibers are obtained by chopped glass fiber plied yarns; and the continuous glass fiber fabric is continuous glass fiber woven cloth.
6. The multi-gradient composite prepreg according to claim 5, characterized in that: The length of the chopped glass fibers is 20-50 mm, and the surface density of the continuous glass fiber fabric is 200-400 g / m 2 .
7. A method for preparing a multi-gradient composite prepreg, characterized in that: The steps include: Step 1, weighing 80-95 parts of epoxy resin, 5-20 parts of active diluent, and 1-15 parts of auxiliary agent in a mixing tank, stirring evenly, and then sequentially adding 5-15 parts of latent curing agent, 1-5 parts of curing accelerator, and 50-150 parts of halogen-free flame retardant, and performing high-speed stirring and dispersion to obtain resin paste A after dispersion; Step 2, after filtering the resin paste A through a 80-100 mesh filter screen, add 3-10 parts of thickener according to proportion, and disperse by high-speed stirring, and obtain resin paste B after dispersion; Step 3, pass the glass fiber plied yarn through the yarn guide tube into the yarn cutting roller through the air gun, pour the resin paste B into the high-position glue tank and the low-position glue tank respectively, start the main machine to move the film, and driven by the carrier film, the resin paste B is scraped out through the gap between the scraper on the glue tank and the table to form a resin film with uniform thickness. The resin film scraped out of the low-position glue tank is the lower resin film, and the resin film scraped out of the high-position glue tank is the upper resin film; Step 4, turning on the front cutting roller and the rear cutting roller, the cutters on the cutting rollers uniformly cut the glass fiber plied yarn into short glass fibers with a length of 20-50 mm, and the short glass fibers freely fall onto the lower resin film in step 3; unfolding the glass fiber woven cloth roll and placing it between the doffing positions of the front cutting roller and the rear cutting roller, or unfolding the continuous glass fiber woven cloth roll and placing it behind the doffing position of the rear cutting roller, and laying the leading edge of the continuous glass fiber woven cloth on the front end of the impregnation zone; The upper resin film is finally covered on the chopped glass fiber or glass fiber woven cloth, and is pulled into the impregnation area by the guide roller. The fiber impregnation is completed under the extrusion of the chain belt, and then it is rolled up and transferred to the drying room for aging. After aging, a multi-gradient composite prepreg is obtained.
8. The method for preparing a multi-gradient composite prepreg according to claim 7, characterized in that: The stirring speed in step 1 is 400-600 r / min, the stirring time is 15-30 min, and the viscosity of the resin paste A is 12000-35000 mPa·S (40° C.); The stirring speed in step 2 is 400-600 r / min, and the stirring time is 3-5 min.
9. The method for preparing a multi-gradient composite prepreg according to claim 7, characterized in that: In the step 3, the carrying film has a film travel speed of 5-8 m / min; and the gap between the scraper and the table is 0.1-1 mm.
10. The method for preparing a multi-gradient composite prepreg according to claim 7, characterized in that: In step 4, the aging temperature is 35-60° C., and the aging time is 3-72 hours.